Аналіз сучасних проблем методики навчання біофізики - Строгонова, Тетяна Василівна; Стучинська, Н.; Strogonova, T. V.; Stuchinskaya, N. (My University, 2020)
У статті проаналізовані актуальні на сучасному етапі проблеми викладання біофізики з позицій реалізації головних принципів дидактики: змістовна складність міждисциплінарних зв'язків біофізики з іншими дисциплінами, узгодженості їх розподілу в часі; обмеженість варіативності навчання та доступності, сучасні можливості реалізації принципу наочності. Запропоновано шляхи вдосконалення методики навчання, які спрямовані на підвищення ефективності організації самостійної роботи й підвищення творчої активності студентів. Автори вивчають дидактичну концепцію та методологію, які були запропоновані українськими дослідженнями в педагогічній галузі протягом останніх років; проаналізували міждисциплінарні зв’язки біофізики з іншими предметами, що навчаються в медичному університеті; були проаналізовані статті, доповіді конференцій та дисертації. The article discusses some methodological problems of teaching biophysics that arise in the implementation of the main principles of training: the content complexity of the interdisciplinary links of biophysics with other subjects, their distribution in time; limited learning and accessibility due to objective factors. Ways to improve teaching methods that are aimed at organizing students 'independent work and enhancing students' creative activity. The authors study didactical concept and methodology, which were proposed by Ukrainian researches in the pedagogical field over last years; analysed interdisciplinary relationships of biophysics with another subject matters studying at the medical university; the papers, studies and transactions were examined. It was estimated that course of biophysics should be based on the relation with, first of all, physiology (normal and pathological), clinical and pathological anatomy, biological chemistry, organic chemistry, physical chemistry, pharmacology, molecular biology and genetics, instrumental methods of functional diagnostics, special medical disciplines (cardiology, therapy, therapy) , oncology and so on. Thus methodology of course has to elicit content of course based on relation with the mentioned above matters.
Analysis of modern problems training of biophysics at medical university
Keywords: біофізика; вища математика; медичний університет; якість викладання; методи викладання; проблеми навчання; принципи навчання; biophysics; higher mathematics; medical university; quality of teaching; teaching methods; problems of teaching; principles of learning